Theranostic Trigger‐Responsive Carbon Monoxide‐Generating Microbubbles. Issue 18 (1st April 2022) - Pathak, Vertika; Roemhild, Karolin; Schipper, Sandra; Groß‐Weege, Nicolas; Nolte, Teresa; Ruetten, Stephan; Buhl, Eva Miriam; El Shafei, Asmaa; Weiler, Marek; Martin, Lukas; Marx, Gernot; Schulz, Volkmar; et al.
Abstract: Carbon monoxide (CO) is a gaseous signaling molecule that modulates inflammation, cell survival, and recovery after myocardial infarction. However, handling and dosing of CO as a compressed gas are difficult. Here, light‐triggerable and magnetic resonance imaging (MRI)‐detectable CO release from dimanganese decacarbonyl (CORM‐1) are demonstrated, and the development of CORM‐1‐loaded polymeric microbubbles (COMB) is described as an ultrasound (US)‐ and MRI‐imageable drug delivery platform for triggerable and targeted CO therapy. COMB are synthesized via a straightforward one‐step loading protocol, present a narrow size distribution peaking at 2 µm, and show excellent performance as a CORM‐1 carrier and US contrast agent. Light irradiation of COMB induces local production and release of CO, as well as enhanced longitudinal and transversal relaxation rates, enabling MRI monitoring of CO delivery. Proof‐of‐concept studies for COMB‐enabled light‐triggered CO release show saturation of hemoglobin with CO in human blood, anti‐inflammatory differentiation of macrophages, reduction of hypoxia‐induced reactive oxygen species (ROS) production, and inhibition of ischemia‐induced apoptosis in endothelial cells and cardiomyocytes. These findings indicate that CO‐generating MB are interesting theranostic tools for attenuating hypoxia‐associated and ROS‐mediated cell and tissue damage in cardiovascular disease. Abstract : Air‐filled polymeric microbubbles are loaded with the carbon monoxide (CO) releasing molecule CORM‐1, which enables local light‐triggered CO generation. Triggered generation of CO is monitored via ultrasound and magnetic resonance imaging and assists in suppressing inflammation and hypoxia‐induced cell death in immune and heart muscle cells.